Estudio de la Talabartería en la Parroquia de Machachi Provincia de Pichincha - Veloz Veloz, Lissette Priscila (2018)
This research project aims to make a recording of the processes of the leather through the saddlery in the parish of the Machachi, which conducted a situational diagnosis of the parish where it is evident that the 42,42% is dedicated to livestock, this being the fundamental axis for the continued existence of the talabarterias because here are useful items for this activity, culturally the chacareria is rooted in the people of the community by the nature of the cattle activity. They were able to identify three talabarterias which were the main source of inquiry to gather information and record the processes of articles that are associated with the talabarterias. To define the processes a search was conducted through the inventory with the implementation of the CPI, there were eleven articles that make the saddlers, as a result were obtained three processes and articles that have already been lost, are vulnerable because they exist only in the memory of the people. The rest remains in force. Once the record is systematized the information obtained to finish with the guidance of the processes of the leather through the saddlery. Descriptive guide to the topic: "El arte en cuero", which highlights the important aspects such as the description of each implement, process, use and techniques of the elements that are within the saddlery. Recognizing that this research is in favor of the different artisans who are dedicated to this activity, and for the parish should be an income, stating that the saddlery within tourism is a new alternative to society. For this reason we recommend that this project will be a primary home for future research by determining that the talabarterias are a historical principle within the parish of Machachi.